Challenges in the assessment of adverse drug reactions in children and neonates. (February 2018) - Bracken, Louise; Nunn, Anthony; Peak, Matthew; Turner, Mark
Abstract : Summary: Adverse drug reactions (ADRs) are common in children and it is often difficult to distinguish ADRs from other underlying conditions. Children range from preterm neonates to adolescents with changing patterns of disease, pharmacokinetics and pharmacodynamics. The continuous development during childhood presents a challenge to developing, prescribing and administering age-appropriate medicines. Paediatric ADRs can be difficult to characterize. There is a lack of agreed definitions, which are needed so that data on ADRs can be consistently reported and reliably interpreted. Many of the adult tools to assess causality and avoidability are difficult to apply in paediatrics. Paediatric ADRs are under-reported in spontaneous reporting systems, and there is little research. Steps addressing the challenges include the Liverpool causality and avoidability assessment tools, improved definitions and more paediatric drug research following the introduction of Paediatric Regulation in 2007, requirement for risk assessment and after marketing surveillance. Advances in assessing susceptibility through pharmacogenomics offer hope of avoiding ADRs.